HUBUNGAN ANTARA SUBJECTIVE WELL-BEING DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PETUGAS CUSTOMER SERVICE DI PLASA TELKOM REGIONAL DIVISION IV - Purwito, Satri; Nurtjahjanti, Harlina; Ariati, Jati (Jurnal Psikologi, 2012)
This study eximined the relationship between subjective well being and organizational citizenship behavior in customer service officer of Plasa Telkom Regional Division IV. Participant in this study were 31 customer service officer from 100 customer service officer in regional division IV. This study used two psychological scale: organizational citizenship behavior scale and subjective well being scale. Organizational citizenship behavior consist of 42 item (Î± = 0, 912). Subjective well being consist of two subscale, cognitive scale consist of 5 item (Î± = 0,841) dan afective subscale consist of 19 item (Î± = 0,905). The result was analyzed using product moment with rxy = 0,506 and p = 0,004 (p < 0,05). Effective contribution of subjective well being for organizational citizenship behavioris 25,6%.Keywords : subjective well-being, organizational citizenship behavior, customer service officer.